Role of Molecular Biology in Cancer Treatment: A Review Article - Aman IMRAN; Hafiza Yasara QAMAR; Qurban ALI; Hafsa NAEEM; Mariam RIAZ; Saima AMIN; Naila KANWAL; Fawad ALI; Muhammad Farooq SABAR; Idrees Ahmad NASIR (Tehran University of Medical Sciences, 2017)
Background: Cancer is a genetic disease and mainly arises due to a number of reasons include activation of oncogenes, malfunction of tumor suppressor genes or mutagenesis due to external factors. Methods: This article was written from the data collected from PubMed, Nature, Science Direct, Springer and Elsevier groups of journals. Results: Oncogenes are deregulated form of normal proto-oncogenes required for cell division, differentiation and regulation. The conversion of proto-oncogene to oncogene is caused due to translocation, rearrangement of chromosomes or mutation in gene due to addition, deletion, duplication or viral infection. These oncogenes are targeted by drugs or RNAi system to prevent proliferation of cancerous cells. There have been developed different techniques of molecular biology used to diagnose and treat cancer, including retroviral therapy, silencing of oncogenes and mutations in tumor suppressor genes. Conclusion: Among all the techniques used, RNAi, zinc finger nucleases and CRISPR hold a brighter future towards creating a Cancer Free World.